2006
DOI: 10.1242/jcs.02942
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of pancreatic β-cell insulin secretion by actin cytoskeleton remodelling: role of gelsolin and cooperation with the MAPK signalling pathway

Abstract: We have previously isolated two MIN6 beta-cell sublines, B1, highly responsive to glucose-stimulated insulin secretion, and C3, markedly refractory (Lilla, V., Webb, G., Rickenbach, K., Maturana, A., Steiner, D. F., Halban, P. A. and Irminger, J. C. (2003) Endocrinology 144, 1368-1379). We now demonstrate that C3 cells have substantially increased amounts of F-actin stress fibres whereas B1 cells have shorter cortical F-actin. Consistent with these data, B1 cells display glucose-dependent actin remodelling whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
154
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 145 publications
(170 citation statements)
references
References 52 publications
(81 reference statements)
16
154
0
Order By: Relevance
“…We have shown that the IRS-2/ Akt/AS160 pathway is involved in GSIS in primary beta cells (9), and a recent report indicates that an IGF-2/IGF-1 receptor autocrine loop underlies the glucose effect on insulin signaling mediated by IRS-2 (17). Moreover, IRS-2 is indispensable for normal beta cell function (12,43), while ERK activation is involved in GSIS (44,45). Our present data indicate that TNF-␣ treatment blocks glucose action on IR, Akt, ERK, and AS160 as well as other Akt substrates.…”
Section: Discussionmentioning
confidence: 57%
“…We have shown that the IRS-2/ Akt/AS160 pathway is involved in GSIS in primary beta cells (9), and a recent report indicates that an IGF-2/IGF-1 receptor autocrine loop underlies the glucose effect on insulin signaling mediated by IRS-2 (17). Moreover, IRS-2 is indispensable for normal beta cell function (12,43), while ERK activation is involved in GSIS (44,45). Our present data indicate that TNF-␣ treatment blocks glucose action on IR, Akt, ERK, and AS160 as well as other Akt substrates.…”
Section: Discussionmentioning
confidence: 57%
“…Supporting this view, we observed altered levels of proteins involved in remodeling the cortical cytoskeleton network-the depolymerizing enzymes Villin 1 and Gelsolin are up and inhibitory enzymes Capza 1 and 2 are down-regulated. Gelsolin's role in this process has already been demonstrated (33). Moreover, ␣-actinin-1 and 4 were up-regulated.…”
Section: Resultsmentioning
confidence: 79%
“…The selective reduction of the second phase of GSIS in Dnm2 KO mice shows striking parallel with the reduced insulin secretion after perturbations of actin remodeling (13)(14)(15)81), a key factor that selectively contributes to the second phase (10,11). Accordingly, enhanced actin disassembly by PPARβ/δ (17) or the actin-capping protein gelsolin (81) increases the second phase.…”
Section: Discussionmentioning
confidence: 99%